Visualisierung sprachlicher Daten Visual Linguistics - Praxis - Tools - Bubenhofer, Noah (Heidelberg University Publishing (heiUP), 2018)
Visualizations play an important role in the scientific research process. They serve to illustrate the knowledge gained, but also as a tool to gain knowledge. Such visualizations are also important in linguistics. For example in the form of maps, tree graphs and word nets. In corpus linguistics, explorative visualizations are often a way to make the data accessible and interpretable. The book reflects on the theoretical basics of scientific visualizations in linguistics, shows practical examples and also introduces visualization tools.